Small, Dense LDL Particle Concentration Correlates with Plasminogen Activator Inhibitor Type-1 (PAI-1) Activity - Väisänen, Sari; Baumstark, Manfred W; Penttilä, Ilkka; Bouchard, Claude; Halonen, Pirjo; Rankinen, Tuomo; Berg, Aloys; Rauramaa, Rainer (Thrombosis and Haemostasis, 1997)
The relation between LDL subtractions and fibrinolytic activity was studied in 150 men aged 53 to 63 years. Apolipoprotein B (apoB) concentration in the most dense LDL-5 (r = 0.39, p <0.001) and LDL-6 (r = 0.43, p <0.001) subtractions associated with plasminogen activator inhibitor type-1 (PAI-1) activity. Subjects in the highest LDL-6 apoB tortile had higher PAI-1 (24.7 vs. 13.1 AU/ml, p <0.001) and lower t-PA (0.26 vs. 0.54 IU/ml, p <0.001) activities than men in the lowest tortile. The difference in PAI-1 remained after adjusting for either triglycerides (p = 0.039) or insulin (p = 0.015) with cardiorespiratory fitness as an additional covariate, and history of cardiovascular disease and smoking as factors. In a regression analysis, plasma insulin and LDL-6 apoB, but not plasma triglycerides and body mass index, entered the model, and explained 30.6 and 3.9 % of the variance in PAI-1 activity, respectively. The novel finding of the present study was the independent association between small, dense LDL particles and PAI-1 activity in middle-aged men.